Insights Into Plant Surgery: An Overview of the Multiple Grafting Techniques for Arabidopsis thaliana - Bartusch, Kai; Melnyk, Charles W. (Frontiers in Plant Science, 2020)
Plant grafting, the ancient practice of cutting and joining different plants, is gaining popularity as an elegant way to generate chimeras that combine desirable traits. Grafting was originally developed in woody species, but the technique has evolved over the past century to now encompass a large number of herbaceous species. The use of plant grafting in science is accelerating largely due to the innovative techniques developed for the model plant Arabidopsis thaliana. Here, we review these developments and discuss the advantages and limitations associated with grafting various Arabidopsis tissues at diverse developmental stages.